Investigation on Machine Learning Approaches for Environmental Noise Classifications - Ali Othman Albaji; Rozeha Bt. A. Rashid; Siti Zeleha Abdul Hamid (Journal of Electrical and Computer Engineering, 2023)
This project aims to investigate the best machine learning (ML) algorithm for classifying sounds originating from the environment that were considered noise pollution in smart cities. Sound collection was carried out using necessary sound capture tools, after which ML classification models were utilized for sound recognition. Additionally, noise pollution monitoring using Python was conducted to provide accurate results for sixteen different types of noise that were collected in sixteen cities in Malaysia. The numbers on the diagonal represent the correctly classified noises from the test set. Using these correlation matrices, the F1 score was calculated, and a comparison was performed for all models. The best model was found to be random forest.